2014
DOI: 10.1517/17460441.2014.927435
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances using zebrafish animal models for muscle disease drug discovery

Abstract: Introduction Animal models have enabled great progress in the discovery and understanding of pharmacological approaches for treating muscle diseases like Duchenne muscular dystrophy. Areas covered With this article, the author provides the reader with a description of the zebrafish animal model, which has been employed to identify and study pharmacological approaches to muscle disease. In particular, the author focuses on how both large-scale chemical screens and targeted drug treatment studies have establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…By 24 hpf, all segmental blocks of muscle, or myotomes (Box 1), are present, partitioned by tendon-like junctions, enabling the embryo to coil and even respond to touch. The muscle becomes fully differentiated by 48 hpf and the larva is freely swimming by 96 hpf (Baxter and Bryson-Richardson, 2018;Stickney et al, 2000;Maves, 2014).…”
Section: Zebrafishmentioning
confidence: 99%
“…By 24 hpf, all segmental blocks of muscle, or myotomes (Box 1), are present, partitioned by tendon-like junctions, enabling the embryo to coil and even respond to touch. The muscle becomes fully differentiated by 48 hpf and the larva is freely swimming by 96 hpf (Baxter and Bryson-Richardson, 2018;Stickney et al, 2000;Maves, 2014).…”
Section: Zebrafishmentioning
confidence: 99%
“…One example is a chemical that was identified that partially ameliorated the muscle phenotype in dystrophin-null zebrafish models of the progressive muscle wasting disorder Duchenne’s muscular dystrophy, which currently is a terminal illness with no effective cure [71, 72]. These zebrafish chemical screen findings were further examined in a mouse model of Duchenne’s muscular dystrophy and found to similarly ameliorate the muscle phenotype in a mammalian animal model [73]. Such discoveries have great potential for translation into clinical applications for Duchenne’s muscular dystrophy by connecting basic research and clinical scientists through international clinical trial networks and patient registries such as the Translational Research in Europe-Assessment and Treatment of Neuromuscular Diseases (TREAT-NMD), Muscular Dystrophy Association, and the Registry of Muscular Dystrophy (Remudy) [47, 74].…”
Section: Fruitful Cross-species Collaborationsmentioning
confidence: 99%
“…Zebrafish are an outstanding model for DMD, particularly for screening and evaluating novel drug therapies (Bassett et al, 2003; Bassett and Currie, 2004; Berger et al, 2010; Maves, 2014; Widrick et al, 2019). A zebrafish dmd mutant strain, also known as sapje , has a nonsense mutation in exon 4 and is a dystrophin-deficient model of DMD (Bassett et al, 2003; Berger et al, 2010; Granato et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…dmd zebrafish exhibit many aspects of human DMD pathology; in particular, skeletal muscle fibrosis and inflammation, including infiltration of mononuclear cells (Bassett and Currie, 2004; Berger et al, 2010). dmd zebrafish offer several advantages for screening and evaluating drugs, including being amenable to rapid and high-throughput screening and affording an exceptional range of approaches for assessing treatment outcomes (Kawahara et al, 2011; reviewed in Maves, 2014 and in Widrick et al, 2019). Zebrafish eggs can be rapidly produced in large numbers, the resulting embryos readily absorb drug compounds, and muscle development and structure can easily be observed in vivo through birefringence techniques (Berger et al, 2012; Granato et al, 1996; Kawahara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%